PEMODELAN DAN STRATEGI COMPETITIVENESS AGRIBISNIS TEMBAKAU BESUKI NA-OOGST DI JAWA TIMUR - Hani, Evita Soliha; Soetriono, Soetriono; Paramu, Hadi (Jurnal Sosial Ekonomi Pertanian, 2009)
Agribusiness of NOTA and NO Traditional Tobacco has competitiveness (comparative and competitive advantage). Moreover, they are susceptible to changes in input and output prices which are indicated by the DRC and PCR coefficient close to 1. The NOTA tobacco is comparatively stronger than the traditional NO tobacco. This illustration has explained that the alternative cultivation technology of NOTA tobacco is better than the traditional NO. Input prices policy by government to NOTA and NO tobacco Traditional agribusiness provided for the development of agroindustry which has NPCI coefficient lower than one (1). It means that the government´s policies provide protection for production inputs. However, the policy is not balanced by a protective policy in output, so that the protective policy has not been very significant input for NOTA and NO Traditional tobacco producers. Overall, government policy is to develop Besuki Na-oogst tobacco both the NOTA and NO Traditional. It is not significant to farmers. It can be explained by the Effective Protection coefficient (EPC) and the Profitability Coefficient (PC) which is lower than one (<1), as well as negative Subsidy Ratio to Producers (SRP). Keyword : Agribussiness tobacco, DRC,PCR,NPCI,EPC,SRP